2008
DOI: 10.1097/qai.0b013e3181642244
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Mental Health and Substance Abuse Care for People Living With HIV/AIDS, Chronic Mental Illness, and Substance Abuse Disorders

Abstract: Among adults with HIV/AIDS and co-occurring MH and SA disorders, utilization of MH and SA services needs to be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 28 publications
4
77
1
Order By: Relevance
“…Despite the benefit of mental health treatment, research data from HCSUS and other studies report that a substantial proportion of HIV-infected individuals with mental illness are not receiving mental health care. 2,19,[33][34][35][36][37][38] For example, a study of individuals with HIV initiating mental health counseling found that nearly 30% did not return after 1 session and only 37% completed 6 counseling sessions. 37 Significant barriers to mental health treatment have been found for HIV-infected individuals including stigma, fear of discrimination, [39][40][41] travel distance to care, 37 and lack of education, 34,42 transportation, 43 insurance, 33,34 service availability, 44,45 and motivation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the benefit of mental health treatment, research data from HCSUS and other studies report that a substantial proportion of HIV-infected individuals with mental illness are not receiving mental health care. 2,19,[33][34][35][36][37][38] For example, a study of individuals with HIV initiating mental health counseling found that nearly 30% did not return after 1 session and only 37% completed 6 counseling sessions. 37 Significant barriers to mental health treatment have been found for HIV-infected individuals including stigma, fear of discrimination, [39][40][41] travel distance to care, 37 and lack of education, 34,42 transportation, 43 insurance, 33,34 service availability, 44,45 and motivation.…”
Section: Introductionmentioning
confidence: 99%
“…However, differences between intervention and control groups were not statistically significant for some of these measures in a number of the studies, especially in regards to patient's improvement in quality-of-life and in one study, the annual cost-savings of health services (Weaver et al 2009). It is nevertheless imperative to be cognizant of the diversity in integration approaches adopted and varying methodologies across the studies.…”
Section: Implications For Researchmentioning
confidence: 99%
“…The percentage attributable to hospital care in both groups decreased, but there were no significant differences between them in annual cost of health services and quality of life. The overall risk of bias for this study was unclear (Weaver et al 2009). …”
Section: Meso-and Micro-level Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Integration of mental health, substance use, and HIV care has been recommended for this population. 1,6,[20][21][22][23] A handful of studies have examined the integration of HIV prevention and treatment into substance use programs, 24,25 as well as integration of substance abuse assessment and interventions into HIV primary medical care. 21,26 More recent work has highlighted provider characteristics and their role in the integration of routine alcohol assessment and brief interventions in the HIV clinic.…”
Section: Introductionmentioning
confidence: 99%